2007
DOI: 10.1200/jco.2006.09.3369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Androgen Suppression Therapy for Prostate Cancer on the Frequency and Timing of Fatal Myocardial Infarctions

Abstract: The use of AST is associated with earlier onset of fatal MIs in men age 65 years or older who are treated for 6 months compared with men who are not treated with AST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
297
2
11

Year Published

2008
2008
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 472 publications
(317 citation statements)
references
References 26 publications
7
297
2
11
Order By: Relevance
“…Several other side effects of castration, including hot flushes, anaemia, and metabolic syndrome, are also increasingly recognised, although others such as cognitive dysfunction require further research to clarify their impact (Sharifi et al, 2005). It has recently been suggested that the use of ADT is associated with earlier onset of fatal myocardial infarction in men aged 65 years or above (D'Amico et al, 2007) and that in patients with locoregional prostate cancer it may be associated with an increase risk of cardiovascular disease not seen with orchidectomy (Keating et al, 2006). An alternative approach is to evaluate agents that are potentially as effective as, or more effective than, LHRH analogues in activity, for example, by achieving castrate levels of testosterone while avoiding some of the side effects of the castration syndrome.…”
mentioning
confidence: 99%
“…Several other side effects of castration, including hot flushes, anaemia, and metabolic syndrome, are also increasingly recognised, although others such as cognitive dysfunction require further research to clarify their impact (Sharifi et al, 2005). It has recently been suggested that the use of ADT is associated with earlier onset of fatal myocardial infarction in men aged 65 years or above (D'Amico et al, 2007) and that in patients with locoregional prostate cancer it may be associated with an increase risk of cardiovascular disease not seen with orchidectomy (Keating et al, 2006). An alternative approach is to evaluate agents that are potentially as effective as, or more effective than, LHRH analogues in activity, for example, by achieving castrate levels of testosterone while avoiding some of the side effects of the castration syndrome.…”
mentioning
confidence: 99%
“…[6][7][8] Furthermore, recent data have linked ADT to an increased risk of cardiovascular morbidity and mortality, including new onset diabetes, coronary artery disease and sudden cardiac death. [9][10][11][12] When ADT fails, patients with hormone-refractory PC have fewer treatment options and a poorer prognosis as the mainstay of therapy is cytotoxic chemotherapy that confers a mere 2-month survival advantage. 13 In recent years, increased attention has focused on exercise as a supportive adjunct therapy following a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Greater risk of cardiovascular death was observed only in the subset of men who underwent radical prostatectomy. A pooled analysis of three small randomized controlled trials of radiation therapy with or without ADT for intermediate and high-risk prostate cancer reported that ADT was associated with shorter time to fatal myocardial infarction [8]. Notably, the analyses included only 51 primary events and the association was observed only in a subset of older men.…”
Section: Do Gnrh Agonists Increase Cardiovascular Mortality?mentioning
confidence: 99%